CURRENT STATE OF THE PROBLEM AMNIOTIC FLUID OUTFLOW IN PREMATURE PREGNANCY - Shavazi, N.N. (Toshkent tibbiyot akademiyasi axborotnomasi, 2020)
Premature birth call the childbirth which occurred at duration of gestation from 22 to 37 (259 days) of weeks or childbirth which happened till 37th week. Most of all factors of the reasons from which it is conditionally possible to distinguish the reasons connected with an organism of mother, a fruit and combined is characteristic of premature births. From all these factors of the premature births (PB) the most significant consider the premature bursting of amniotic waters (PBAW). In modern literature there is no unambiguous opinion on an etiology and a pathogenesis of PBAW. For the purpose of decrease in the perinatal incidence and mortality connected with this pathology there is a need of further studying of PIOV mechanisms at the molecular and cellular levels.